2014
DOI: 10.5999/aps.2014.41.1.63
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perforator Number on Deep Inferior Epigastric Perforator Flap Breast Reconstruction

Abstract: BackgroundPerforator flaps minimize abdominal site morbidity during autologous breast reconstruction. The purpose of this study was to assess whether the number of perforators harvested influences the overall deep inferior epigastric perforator (DIEP) flap survival and flap-related complications.MethodsA retrospective review was performed of all DIEP flaps performed at the Hospital of the University of Pennsylvania from 2006 to 2011. The outcomes assessed included flap loss and major complications. We compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 21 publications
2
58
0
4
Order By: Relevance
“…This finding is supported from a theoretical point of view by Patel and Keller [24]. However, other studies, for instance by Grover et al [25] and Baumann et al [26], show that the rate of fat necrosis is higher in DIEP flaps based on a single perforator. In the present study, we found no difference in complication rates depending on the number of perforators.…”
Section: Discussionmentioning
confidence: 73%
“…This finding is supported from a theoretical point of view by Patel and Keller [24]. However, other studies, for instance by Grover et al [25] and Baumann et al [26], show that the rate of fat necrosis is higher in DIEP flaps based on a single perforator. In the present study, we found no difference in complication rates depending on the number of perforators.…”
Section: Discussionmentioning
confidence: 73%
“…Despite a statistical increase of flap perforators, the complication rate remained stable. Moreover, in a recent study, Grover et al demonstrated that the number of perforators had no impact on the rate of flap survival and found a significantly higher rate of fat necrosis in the case of one-perforator flaps than in the case of multiple-perforator flaps [23].…”
Section: Discussionmentioning
confidence: 98%
“…4,6,9,18,19 The use of single perforators has been associated with higher rates of fat necrosis in clinical studies 18 and up to 25 percent in single-dominant perforator DIEP flaps. 4,6,9,18,19 The use of single perforators has been associated with higher rates of fat necrosis in clinical studies 18 and up to 25 percent in single-dominant perforator DIEP flaps.…”
Section: Discussionmentioning
confidence: 99%
“…9 (See Video, Supplemental Digital Content 4, which shows the perforator exploration and dissection and intramuscular pedicle dissection of the DIEP flap with preservation of traversing motor nerves to the rectus muscle, available in the "Related Videos" section of the full-text article on PRSJournal.com or, for Ovid users, available at http://links.lww.com/PRS/B884.) 9 (See Video, Supplemental Digital Content 4, which shows the perforator exploration and dissection and intramuscular pedicle dissection of the DIEP flap with preservation of traversing motor nerves to the rectus muscle, available in the "Related Videos" section of the full-text article on PRSJournal.com or, for Ovid users, available at http://links.lww.com/PRS/B884.)…”
Section: Pedicle Dissectionmentioning
confidence: 99%